Emergence of carbapenemase-producing Klebsiella pneumoniae of sequence type 258 in Michigan, USA - Ruchika Jain; Seth T. Walk; David M. Aronoff; Vincent B. Young; Duane W. Newton; Carol E. Chenoweth; Laraine L. Washer (MDPI AG, 2013)
The prevalence of carbapenemase-producing Enterobacteriaceae (CPE) in our hospital increased beginning in 2009. We aimed to study the clinical and molecular epidemiology of these emerging isolates. We performed a retrospective review of all adult patients with clinical cultures confirmed as CPE by positive modified Hodge test from 5/2009-5/2010 at the University of Michigan Health System (UMHS). Clinical information was obtained from electronic medical records. Available CPE isolates were analyzed by polymerase chain reaction (PCR) and sequencing of the 16S rRNA encoding gene and blaKPC locus. Multilocus sequence typing (MLST) was used to characterize Klebsiella pneumoniae isolates. Twenty six unique CPE isolates were obtained from 25 adult patients. The majority were Klebsiella pneumoniae (n=17). Other isolates included K. oxytoca (n=3), Citrobacter freundii (n=2), Enterobacter cloacae (n=2), Enterobacter aerogenes (n=1) and Escherichia coli (n=1). Molecular characterization of 19 available CPE isolates showed that 13 (68%) carried the KPC-3 allele and 6 (32%) carried the KPC-2 allele. Among 14 available K. pneumoniae strains, 12 (86%) carried the KPC-3 allele and belonged to a common lineage, sequence type (ST) 258. The other 2 (14%) K. pneumoniae isolates carried the KPC-2 allele and belonged to two unique STs. Among these ST 258 strains, 67% were isolated from patients with prior exposures to health care settings outside of our institution. In contrast, all CPE isolates carrying the KPC-2 allele and all non ST 258 CPE isolates had acquisition attributable to our hospital. Molecular epidemiology of carbapenemase producing K. pneumoniae suggests that KPC-3 producing K. pneumoniae isolates of a common lineage, sequence type (ST 258), are emerging in our hospital. While ST 258 is a dominant sequence type throughout the United States, this study is the first to report its presence in Michigan.